2021
DOI: 10.1136/neurintsurg-2020-017232
|View full text |Cite
|
Sign up to set email alerts
|

Woven EndoBridge device shape modification can be mitigated with an appropriate oversizing strategy: a VasoCT based study

Abstract: BackgroundThe Woven EndoBridge (WEB) shape modification (WShM) during follow-up may be a potential cause of poor angiographic outcomes. WShM predisposing factors have not yet been determined. Our systematic use of rotational cone beam computed tomography (VasoCT) imaging during follow-up allowed us to perform the first quantitative analysis of the shape of WEBs over time. Our goal was to identify possible strategies to reduce the occurrence of this phenomenon.MethodsAll patients treated in our hospital with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…1 months): 47.8% and 39.6%, respectively. 44 This study also showed that the extent of WEB shape modification did not directly correlate with anatomical results and that an appropriate WEB oversizing strategy mitigated WEB shape modification and could lead to improved angiographic results. Another recent series (32 aneurysms) that defined WEB shape modification as any reduction in WEB device height greater than 5% reported the phenomenon in 90.6% of aneurysms.…”
Section: Web Shape Modificationmentioning
confidence: 73%
“…1 months): 47.8% and 39.6%, respectively. 44 This study also showed that the extent of WEB shape modification did not directly correlate with anatomical results and that an appropriate WEB oversizing strategy mitigated WEB shape modification and could lead to improved angiographic results. Another recent series (32 aneurysms) that defined WEB shape modification as any reduction in WEB device height greater than 5% reported the phenomenon in 90.6% of aneurysms.…”
Section: Web Shape Modificationmentioning
confidence: 73%
“…The Woven EndoBridge (WEB) device (Microvention, CA) currently represents the most extensively studied intrasaccular device,1 2 and has proven to be a very safe option to treat wide-necked bifurcation aneurysms 3. Since its introduction, angiographic results have improved year on year, likely due to the sharing of operator experiences in device sizing,4 5 and yet 5–12% of patients still require retreatment 3 6–10…”
Section: Introductionmentioning
confidence: 99%
“…Whether WEB shape modification reflects ‘retraction’ or ‘compaction’ of the WEB device is still disputed in the literature (presumably both)15 21; but our results suggest it should be avoided anyway. In their recent publication, Caroff et al proposed to use a WEB oversizing strategy to prevent the shape modification of the WEB, as both were significantly correlated 22…”
Section: Discussionmentioning
confidence: 99%